Áreas verdes urbanas como elemento da cidade sustentável - Matias, Jefferson Ortiz (2006)
The present work had the purpose to analyze the urban green areas, as indispensable element to reach the concept of sustainable city, subscribed in the Statute of the City, Law 10,257/2001, in its article 2o., II, where it is described as a city where its inhabitant has guarantee of the right to the urban land, the housing, the ambient sanitation, the urban infrastructure, the public transport and services, the work and the leisure, for the present and future generations. The green areas, even so it is not mentioned as specifically integrant of the formatting elements of the sustainable city, are indispensable for its formation, since it exerts vital functions in the urban ecosystem, such as the social, ecological, educational and aesthetic function, providing reduction in the urban pollution rates, creating shadows for the passer-bys, best acclimatization and protection for intensive winds, also working as space for diversion and leisure, being able to serve in such as local of primary studies directed toward the infantile public and for academic researches as well, and propitiating the aesthetic increasing, promoting the hygienic improvement and the consequence valuation of the urban area where it stands. All these elements lead to increase the population s quality of life, accurately the main point in the sustainable city s persecution, which is a citizen s right.